Classification of Quality Management Methods - Wawak, Sławomir (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
A catalogue of methods will help scientists studying management and decision-makers in business alike as it allows them to select and use appropriate tools. In the literature, there is no shortage of classification of quality management methods. However, they are mostly incomplete or ambiguous. This paper presents an overview of approaches to the classification of management methods and proposes two suggestions for classifying quality management methods.